INTELLIGENT MANAGMENT OF THE UNBALANCE SUPPLY CHAIN AND DEMAND IN THE LABOR MARKET FOR IT SPECIALISTS - Mammadova, Masuma; Q. jabrayilova, Zarifa; R. mammadzada, Faiq (International Journal of Supply Chain Management, 2018)
Supply chain management that interrelates and integrates both consumers and suppliers into a process to make product value or service to consumers is very important and strategic. The purpose of this work is to develop models and methods to assess the supply chain imbalance and labor market demand based on intellectual control for the IT segment. The labor market operates in conditions of uncertainty and is characterized by specific management tasks, for which there are no ready-made software products and classical mathematical models. In this paper, the authors used fuzzy set theory, which allows the development of formal methods of evaluation and decision support to automate the process of analysis of the supply chain and demand in the labor market. The labor market in the model is described as an intelligent space, in which the main actors representing demand and supply interact. Based on this concept, a simulation of the supply chain interaction and micro-level demand is performed and an algorithm based on fuzzy situational analysis and fuzzy pattern recognition is developed. Suggested in the article methodological approach to the creation of the intelligent management system for the labor market of IT specialists, allows developing management decisions aimed at reducing the (qualitative) discrepancy of supply chain skills and demand. Keywords- Labor market, IT specialists, unbalance supply chain, Fuzzy sets, Intelligent management, Pattern recognition.